2003
DOI: 10.1002/jms.464
|View full text |Cite
|
Sign up to set email alerts
|

Low‐temperature SIMS mass spectra of diethyl ether

Abstract: For the first time a secondary ion mass spectrum of diethyl ether was obtained at low temperature. The spectrum recording became possible by carefully selecting the range of experimental conditions for the production of a cluster-type spectrum. This range is specified by the threshold for spectrum appearance above the melting temperature of the frozen sample and a fairly short time span of existence of the liquid estimated as only a few minutes. The latter necessitates rather rapid spectrum detection. In pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…Our experimental observations are in agreement with theoretical estimates of R evap for different compounds. For example, highly volatile diethyl ether survives in the liquid state for only several minutes after melting,22 while an ethanol sample lasts for hours slightly above its melting temperature 11…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our experimental observations are in agreement with theoretical estimates of R evap for different compounds. For example, highly volatile diethyl ether survives in the liquid state for only several minutes after melting,22 while an ethanol sample lasts for hours slightly above its melting temperature 11…”
Section: Resultsmentioning
confidence: 99%
“…The results of our recent studies of various types of compounds in a wide temperature range of about 200°C, using ambient and low‐temperature (LT) FAB‐SIMS,6–23 have revealed a number of facts which can substantiate Vestal's model. First, the existence of not only a quantitative but a qualitative difference between characteristics of sputtering from the same substance in the solid and liquid states was demonstrated experimentally 10,13,14,17–23. Then, a simple estimate has shown that all liquids ever studied under FAB conditions were in a superheated state under the mass spectrometric vacuum.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…10,11 Cluster ion formation from selected cooled matrices, especially from alcohols and water, became the focus of low-temperature mass spectrometric measure-ments. [12][13][14][15][16] Important features of phase transitions in the lowtemperature range were mapped out, yielding information relating to cryochemistry and cryobiophysics. 12,13 Methanol clusters have been studied by a variety of techniques, with a view to probing structure, binding energy and dissociation dynamics and proton transfer.…”
Section: Introductionmentioning
confidence: 99%